2007
DOI: 10.1016/j.bbrc.2007.01.137
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelial glycocalyx components in mechanotransduction of fluid shear stress

Abstract: The surface of endothelial cells is decorated with a wide variety of membrane-bound macromolecules that constitute the glycocalyx. These include glycoproteins bearing acidic oligosaccharides with terminal sialic acids (SA), and proteoglycans with their associated glycosaminoglycan that include: heparan sulfate (HS), chondroitin sulfate (CS) and hyaluronic acid (HA). In this study enzymes were used to selectively degrade glycoclyx components from the surface of bovine aortic endothelial cells and the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
354
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 343 publications
(371 citation statements)
references
References 28 publications
13
354
1
3
Order By: Relevance
“…2006c) and perhaps eNOS phosphorylation by a glycocalyx‐linked deformation of caveolae (Pahakis et al . 2007). Importantly, the present study demonstrates that a decreased shear stress after the cessation of vasodilator therapy leads to a decrease in eNOS expression, a key mediator of shear stress‐induced angiogenesis: vessel growth is absent in eNOS‐knockout mice (Williams et al .…”
Section: Discussionmentioning
confidence: 99%
“…2006c) and perhaps eNOS phosphorylation by a glycocalyx‐linked deformation of caveolae (Pahakis et al . 2007). Importantly, the present study demonstrates that a decreased shear stress after the cessation of vasodilator therapy leads to a decrease in eNOS expression, a key mediator of shear stress‐induced angiogenesis: vessel growth is absent in eNOS‐knockout mice (Williams et al .…”
Section: Discussionmentioning
confidence: 99%
“…Flow sensing properties likely reside in the luminal endothelial surface; constituted by the cell membrane and glycocalyx which is acted by flow [6][7][8][9][10][11][12][13]. We have shown that flowinduced responses require endothelial surface layer oligosaccharides and oligosaccharide-recognizing proteins, lectins because a) specific enzymatic hydrolysis of endogenous oligosaccharides or their binding to exogenous lectins exactly alter flow-induced responses and b) infusion of diverse exogenous oligosaccharides that bind to endothelial surface lectins alter the effects of flow [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the roles of individual endothelial surface sugars and lectins in flow-induced responses are function biased; a complexity that makes difficult to identify the exact "mechanosensor(s)" for each response [6,8,[10][11][12][13]15]. In contrast, in the case of a defined G-protein coupled receptor, the response triggered by its specific agonist identifies it as the structure of origin, the agonist-sensor [1,3,4,14].…”
Section: Introductionmentioning
confidence: 99%
“…The glycocalyx layer has been described as a mechanosensor and transducer of FSS on ECs [1,5,[25][26][27][28][29][30][31][32][33][34][35][36]. Theoretical models to describe the transmission of force from fluid flow to the surface of cells covered by glycocalyx have revealed & 2014 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%